THE ROLE OF HELICOBACTER PYLORI IN CHRONIC SPONTANEOUS URTICARIA: FROM PATHOGENESIS TO CLINICAL IMPLICATIONS - Anna Kamosińska; Julia Pająk; Antoni Majda; Natalia Sitko; Paulina Makowska; Joanna Gontarczyk; Alicja Laske; Martyna Sowa; Kacper Kucharski; Adam Kowal; Julia Sokołowska; Marcel Dawidowicz (International Journal of Innovative Technologies in Social Science, 2026)
Background: Chronic spontaneous urticaria (CSU) is characterized by the presence of pruritic wheals persisting for more than 6 weeks, which may or may not be accompanied by angioedema. In recent years, increasing attention has been given to the potential role of infectious factors in the pathogenesis of CSU, including Helicobacter pylori infection, which may represent a contributing factor to disease exacerbation. Objective: This review aims to evaluate the association between H. pylori infection and chronic spontaneous urticaria. It addresses underlying pathophysiological mechanisms, the impact of bacterial eradication on clinical symptoms, and the clinical relevance of diagnostic and therapeutic approaches. Methods: A literature review was conducted to assess the association between H. pylori infection and chronic spontaneous urticaria. Studies addressing disease pathomechanisms, the impact of bacterial eradication on the clinical course, and the role of diagnostic and therapeutic strategies were analyzed. Both clinical studies and meta-analyses published in peer-reviewed medical journals were included. Results: H. pylori infection is more frequently observed in patients with CSU, although its prevalence does not consistently exceed that in the general population. Symptomatic improvement following bacterial eradication has been reported in some patients; however, the correlation remains inconclusive. Conclusions: H. pylori infection may influence the course of chronic spontaneous urticaria by modulating immune responses and inflammatory processes, which may partly explain symptomatic improvement following eradication. However, study findings remain inconsistent, and limitations such as small patient cohorts and heterogeneity of treatment regimens hinder a definitive assessment of the bacterium’s role in the disease.